Paraoxonase/Arylesterase Activity of Serum Paraoxonase-1 and Schizophrenia: A Systematic Review and Meta-Analysis - Angelo Zinellu; Stefania Sedda; Arduino A. Mangoni (MDPI AG, 2023)
The presence of a pro-oxidant state in patients with schizophrenia may account for the increased risk of atherosclerosis and cardiovascular disease in this group and supports the potential utility of circulating biomarkers of oxidative stress for risk stratification and management. We investigated this issue by conducting a systematic review and meta-analysis of the association between the circulating concentrations of paraoxonase-1, an antioxidant calcium-dependent high-density lipoprotein (HDL)-associated esterase, with paraoxonase and arylesterase activity in schizophrenia. We searched electronic databases from inception to 31 May 2023 for studies investigating paraoxonase-1 in patients with schizophrenia and healthy controls and assessed the risk of bias and the certainty of evidence (PROSPERO registration number: CRD42023435442). Thirteen studies were identified for analysis. There were no significant between-group differences in paraoxonase (standard mean difference, SMD = 0.12, 95% CI −0.23 to 0.48, p = 0.50; extremely low certainty of evidence) or arylesterase activity (SMD = −0.08, 95% CI −0.39 to 0.23, p = 0.61; very low certainty of evidence). However, in meta-regression and subgroup analysis we observed significant associations between the SMD of paraoxonase and age (p = 0.003), HDL-cholesterol (p = 0.029), and study country (p = 0.04), and the SMD of arylesterase and age (p = 0.007), body mass index (p = 0.012), HDL-cholesterol (p = 0.002), and pharmacological treatment for schizophrenia (p < 0.001). In the absence of overall between-group differences, our systematic review and meta-analysis suggests that alterations in paraoxonase-1 may reflect a pro-oxidant state in specific subgroups of patients with schizophrenia that require further assessment in appropriately designed studies.